Biochemistry and genetics of ACC deaminase: a weapon to “stress ethylene” produced in plants - Singh, Rajnish P.; Shelke, Ganesh M.; Kumar, Anil; Jha, Prabhat N. (Frontiers in Microbiology, 2015)
1-aminocyclopropane-1-carboxylate deaminase (ACCD), a pyridoxal phosphate dependent enzyme, is widespread in diverse bacterial and fungal species. Owing to ACCD activity, certain plant associated bacteria help plant to grow under biotic and abiotic stresses by decreasing level of 'stress ethylene' which is inhibitory to plant growth. ACCD breaks down ACC, an immediate precursor of ethylene, to ammonia and α-ketobutyrate which can be further metabolized by bacteria for their growth. ACC deaminase is an inducible enzyme whose synthesis is induced in presence of its substrate ACC. This enzyme, encoded by gene AcdS, is under tight regulation and regulated differentilly under different environmental conditions. Regulatory elements of gene AcdS are comprised of regulatory gene encoding LRP protein and other regulator elements which are activated differentially under aerobic and anaerobic conditions. Role of some additional regulatory genes such as AcdB or LysR may also be required for expression of AcdS. Phylogenetic analysis of AcdS has revealed that distribution of this gene among different bacteria might have resulted from vertical gene transfer with occasional horizontal gene transfer. Application of bacterial AcdS gene has been extended by developing transgenic plants with ACCD gene which showed increased tolerance to biotic and abiotic stresses in plants. Moreover, distribution of ACCD gene or its homologs in wide range of species belonging to all three domains indicate alternative role of ACCD in physiology of an organism. Therefore, this review is an attempt to explore current knowledge of bacterial ACC deaminase mediated physiological effects in plants, mode of enzyme action, genetics, and distribution in different species and ecological role of ACCD and, future research avenues to develop transgenic plants expressing foreign AcdS gene to cope with biotic and abiotic stressors. Systemic identification of regulatory circuits would be highly valuable to express the